Download presentation
Presentation is loading. Please wait.
Published byGyles Pearson Modified over 9 years ago
1
Converting Quadratic Equations A step-by-step guide with practice
2
Intercept Form to Standard Form Write the equation in standard form: y = – 2(x + 3)(x – 2)
3
Intercept Form to Standard Form Write the equation in standard form: y = – 2(x + 3)(x – 2) y = – 2(x 2 + x – 6) multiply binomials
4
Intercept Form to Standard Form Write the equation in standard form: y = – 2(x + 3)(x – 2) y = – 2(x 2 + x – 6) multiply binomials y = – 2x 2 – 2x + 12 distribute coefficient
5
Vertex Form to Standard Form Write this equation in standard form: y = 2(x – 3) 2 + 4
6
Vertex Form to Standard Form Write this equation in standard form: y = 2(x – 3) 2 + 4 y = 2(x 2 – 6x + 9) + 4 square the binomial
7
Vertex Form to Standard Form Write this equation in standard form: y = 2(x – 3) 2 + 4 y = 2(x 2 – 6x + 9) + 4 square the binomial y = 2x 2 – 12x + 18 + 4 distribute
8
Vertex Form to Standard Form Write this equation in standard form: y = 2(x – 3) 2 + 4 y = 2(x 2 – 6x + 9) + 4 square the binomial y = 2x 2 – 12x + 18 + 4 distribute coefficient y = 2x 2 – 12x + 22 combine like terms
9
Standard Form to Intercept Form Write the equation in intercept form: y = – 15x 2 + 3x + 12
10
Standard Form to Intercept Form Write the equation in intercept form: y = – 15x 2 + 3x + 12 y = – 3(5x 2 – x – 4) factor out GCF
11
Standard Form to Intercept Form Write the equation in intercept form: y = – 15x 2 + 3x + 12 y = – 3(5x 2 – x – 4)factor out GCF y = – 3(5x + 4)(x – 1) factor the trinomial
12
Standard Form to Vertex Form Write the equation in vertex form: y = 3x 2 – 6x + 8
13
Standard Form to Vertex Form Write the equation in vertex form: y = 3x 2 – 6x + 8 y = 3(x 2 – 2x ) + 8group x terms & factor out “a”
14
Standard Form to Vertex Form Write the equation in vertex form: y = 3x 2 – 6x + 8 y = 3(x 2 – 2x ) + 8group x terms & factor out “a” y = 3(x 2 – 2x + 1) + 8 – 3 complete the square
15
Standard Form to Vertex Form Write the equation in vertex form: y = 3x 2 – 6x + 8 y = 3(x 2 – 2x ) + 8 group x terms & factor out “a” y = 3(x 2 – 2x + 1) + 8 – 3 complete the square y = 3(x – 1) 2 + 5 factor and combine
16
Vertex Form to Intercept Form Write the equation in intercept form: y = (x + 4) 2 - 1
17
Vertex Form to Intercept Form Write the equation in intercept form: y = (x + 4) 2 - 1 y = x 2 + 8x + 16 - 1 square the binomial
18
Vertex Form to Intercept Form Write the equation in intercept form: y = (x + 4) 2 - 1 y = x 2 + 8x + 16 - 1 square the binomial y = x 2 + 8x + 15combine terms
19
Vertex Form to Intercept Form Write the equation in intercept form: y = (x + 4) 2 - 1 y = x 2 + 8x + 16 - 1 square the binomial y = x 2 + 8x + 15 combine terms y = (x + 3)(x + 5)factor
20
Intercept Form to Vertex Form Write the equation in vertex form: y = (x – 3)(x + 1)
21
Intercept Form to Vertex Form Write the equation in vertex form: y = (x – 3)(x + 1) y = x 2 – 2x - 3 foil
22
Intercept Form to Vertex Form Write the equation in vertex form: y = (x – 3)(x + 1) y = x 2 – 2x - 3 foil y = x 2 – 2x - 3 get ready to complete the square y = x 2 – 2x + 1 – 3 – 1complete the square
23
Intercept Form to Vertex Form Write the equation in vertex form: y = (x – 3)(x + 1) y = x 2 – 2x - 3 foil y = x 2 – 2x - 3 get ready to complete the square y = x 2 – 2x + 1 – 3 – 1complete the square y = (x - 1) 2 - 4factor and combine
Similar presentations
© 2025 SlidePlayer.com Inc.
All rights reserved.